Dimensionamento à falha distorcional via método da resistência direta de vigas de aço em perfil formado a frio sob flexão não-uniforme - Depolli, Isis Cler (2018)
An in-depth numerical investigation by provided solid evidence that the current Direct Strength Method (DSM) beam distortional strength curve overestimates the ultimate strength of cold-formed steel simply supported beams, thus leading to unsafe designs — the beams analyzed were uniformly bent. Moreover, used the distortional failure moment data obtained to propose new DSM beam distortional design curves, differing visibly from the current one for moderate-to-high slenderness. This dissertation, which may be viewed as a continuation of the aforementioned investigation, concerns the distortional post-buckling behavior and DSM design of simply supported cold-formed steel beams buckling and failing in distortional modes under non-uniform bending due to unequal end moments – five bending moment diagrams (including uniform bending, for comparison purposes) are considered. As in previous studies, two beam simply supported end conditions are considered, differing in the end cross-section warping and local displacements/rotations, which may be either completely free or fully prevented. After acquiring in-depth insight on how the bending moment diagram influences the beam distortional buckling and post-buckling behaviors, an extensive numerical (shell finite element) parametric study is carried out with various cross-section dimension ratios and yield stresses. These failure moments, together with additional values collected from the literature, are then employed to assess the merits of the available DSM beam distortional strength curves in predicting them, and also to propose slight adjustments/modifications aimed at achieving DSM design curves able to provide accurate failure moment predictions that take into account the variation of the bending moment diagram.